1981
DOI: 10.1192/bjp.139.4.288
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography and the Outcome of Affective Disorder: A Follow-up Study of Elderly Patients

Abstract: Forty-one subjects from an earlier study, who had undergone computed tomography (CT) during their in-patient care for affective disorder, were followed up clinically for a minimum of one year. Mortality at two years was also determined, and comparisons made with 50 age-matched controls. Those with affective disorder showed a higher mortality than controls, but the difference just failed to reach significance. Within the affective group, however, mortality was significantly higher in patients who had previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(40 citation statements)
references
References 14 publications
3
35
0
2
Order By: Relevance
“…This finding is certainly consistent with our previous reports demonstrating the importance of differentiating major from dysthymic poststroke depression. 5 " 7 It is also consistent with the findings of Jacoby et al 21 and Post, 22 who found that depression in the elderly is frequently associated with a poor prognosis, particularly when there was associated ventricular enlargement.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is certainly consistent with our previous reports demonstrating the importance of differentiating major from dysthymic poststroke depression. 5 " 7 It is also consistent with the findings of Jacoby et al 21 and Post, 22 who found that depression in the elderly is frequently associated with a poor prognosis, particularly when there was associated ventricular enlargement.…”
Section: Discussionsupporting
confidence: 81%
“…It has been hypothesized that LOD may have a different etiology, characterized by less family history of depression (Baron et al, 1981) and greater comorbid illness (Jacoby et al, 1981). Greater comorbidity has been hypothesized to result in a higher degree of neuroanatomical pathology, including increased white matter hyperintensities (Krishnan et al, 1997) and interruption in white matter tracts between basal ganglia and frontal cortex, potentially involving loss of cells with 5-HT 2A receptors.…”
Section: Introductionmentioning
confidence: 99%
“…However, 2-year follow-up studies showed that elderly depressed patients with CT changes comparable in magnitude with those of patients with AD were not cases of missed Alzheimer's disease (Jacoby et al, 1981;Pearlson et al, 1989). So at least in the short term the cerebral changes accompanying depression in some elderly patients do not predict an eventual progression to dementia.…”
Section: Discussionmentioning
confidence: 95%